Pengaruh Model Pembelajaran Bermain Peran terhadap Kesadaran Antiperundungan Peserta Didik pada Mata Pelajaran PAI - Salamudin, Ceceng; Husniah, Azkia (MASAGI : Jurnal Pendidikan Agama Islam, 2025)
The problem of bullying in schools is a major concern because of its detrimental impact on students' mental and social development, and many students are not yet fully aware of the negative impacts of bullying and the importance of building mutual respect among each other. Therefore, it is important for schools to instill anti-bullying awareness in students to create a safe and harmonious learning environment. One approach that is considered effective in increasing anti-bullying awareness is by using a role-playing learning model, which allows students to understand the situations and feelings of others through direct experience. The purpose of this study is to describe the effect of implementing a role-playing learning model on students' anti-bullying awareness in the Islamic Religious Education Phase D subject. This study uses a quantitative approach with a descriptive method. The data collection methods used are observation, documentation studies, and questionnaires. The research objects were 82 Phase D students. The results showed that the role play learning model had an effect on the anti-bullying awareness of Phase D students by 82.7% at a significance level with a predetermined probability value of 5% and was proven by the Adjusted R Square value of 0.827 if it was expressed as a percentage of 82.7% while other variables that were not studied influenced the personal awareness of students by 17.3%. Keywords: learning model (role play), bullying awareness, learning of pai fhase d